Renal cystic disease in tuberous sclerosis: role of the polycystic kidney disease 1 gene. - Sampson, J R (1997)
Tuberous sclerosis is an autosomal dominant trait characterized by the development of hamartomatous growths in many organs. Renal cysts are also a frequent manifestation. Major genes for tuberous sclerosis and autosomal dominant polycystic kidney disease, TSC2 and PKD1, respectively, lie adjacent to each other at chromosome 16p13.3, suggesting a role for PKD1 in the etiology of renal cystic disease in tuberous sclerosis. We studied 27 unrelated patients with tuberous sclerosis and renal cystic disease. Clinical histories and radiographic features were reviewed, and renal function was assessed. We sought mutations at the TSC2 and PKD1 loci, using pulsed field- and conventional-gel electrophoresis and FISH. Twenty-two patients had contiguous deletions of TSC2 and PKD1. In 17 patients with constitutional deletions, cystic disease was severe, with early renal insufficiency. One patient with deletion of TSC2 and of only the 3' UTR of PKD1 had few cysts. Four patients were somatic mosaics; the severity of their cystic disease varied considerably. Mosaicism and mild cystic disease also were demonstrated in parents of 3 of the constitutionally deleted patients. Five patients without contiguous deletions had relatively mild cystic disease, 3 of whom had gross rearrangements of TSC2 and 2 in whom no mutation was identified. Significant renal cystic disease in tuberous sclerosis usually reflects mutational involvement of the PKD1 gene, and mosaicism for large deletions of TSC2 and PKD1 is a frequent phenomenon.